Reduced vagal activity in borderline personality disorder is unaffected by intranasal oxytocin administration, but predicted by the interaction between childhood trauma and attachment insecurity: psychiatry and preclinical psychiatric studies - Back, Sarah Naomi; Schmitz, Marius; Koenig, Julian; Zettl, Max; Kleindienst, Nikolaus; Herpertz, Sabine; Bertsch, Katja (Journal of neural transmission, 2022)
Individuals with borderline personality disorder (BPD) show self-regulatory deficits, associated with reduced heart-rate variability (HRV). However, results on reduced HRV in BPD remain heterogeneous, thus encouraging the search for developmental constructs explaining this heterogeneity. The present study first examined predictors of reduced resting-state HRV in BPD, namely the interaction between self-reported adult attachment insecurity and childhood trauma. Second, we investigated if alterations in resting-state HRV are modified by intranasal oxytocin administration, as oxytocin may enhance HRV and is implicated in the interaction between childhood trauma and disturbed attachment for the pathogenesis of BPD. In a randomized, placebo-controlled trial, 53 unmedicated women with BPD and 60 healthy controls (HC) self-administered either 24 I.U. of oxytocin or placebo and underwent a 4-min electrocardiogram. Our results replicate significantly reduced HRV in women with BPD, explained up to 16% by variations in childhood trauma and attachment insecurity. At high levels of acute attachment insecurity, higher levels of childhood trauma significantly predicted reduced HRV in BPD. However, our results do not support a significant effect of oxytocin on mean HRV, and no interaction effect emerged including childhood trauma and attachment insecurity. Our findings highlight a complex interaction between reduced vagal activity and developmental factors in BPD.